Observational Study on Secondary Bacterial Infection and the Use of Antibiotics in COVID-19 Patients Treated in a Tertiary Referral Hospital - Khie Chen Lie; Sharifah Shakinah; Adeline Pasaribu; Robert Sinto; Leonard Nainggolan (Acta Medica Indonesiana)
Background: Data on secondary bacterial infection in patients with COVID-19 in Indonesia are still limited, while the use of empirical antibiotics continues to increase. This study aims to determine the secondary bacterial infection rate in hospitalized COVID-19 patients and factors related to secondary bacterial infection. Methods: This is a retrospective cohort study on hospitalized COVID-19 patients undergoing treatment at Cipto Mangunkusumo Hospital from March 2020 to September 2020. Secondary bacterial infection is defined as the identification of a bacterial pathogen from a microbiological examination. Results: From a total of 255 subjects, secondary infection was identified in 14.5%. Predictors of secondary infection were early symptoms of shortness of breath (OR 5.31, 95% CI 1.3 – 21.5), decreased consciousness (OR 4.81, 95% CI 1.77 – 13.0), length of stay > 12 days (OR 8.2, 95% CI 2.9 – 23.3), and central venous catheter placement (OR 3.0, 95% CI 1.1 – 8.0) The most common pathogen of secondary bacterial infection is Acinetobacter sp. (n=9; 28%). Empirical antibiotics were administered to 82.4% of subjects with predominant use of macrolides (n=141; 32.4%). Conclusion: The secondary bacterial infection rate in COVID-19 was 14.5% and is associated with dyspnea, decreased consciousness, length of stay >12 days, and central venous catheter placement. The use of antibiotics in COVID-19 reaches 82.4% and requires special attention to prevent the occurrence of antibiotic resistance.